The role of women in political activism in pre and post-colonial Yoruba history: lessons for contemporary society (2024)
Women are stakeholders in every aspect of human endeavor. Their roles can be seen in the economy, social, religion and political system of every society particularly in Yoruba society of south western Nigeria where they were/are not found wanting in the aforementioned areas of life, most especially in the political field that men often dominate. Even in the times of the gods, the role that Osun, goddess of river Osun played in the political administration of the world then for the recognition of women fold amongst the male gods sent to the earth by Olodumare, the supreme God in Yoruba belief, earned women their due respect till today. In pre-and post-colonial history of the Yoruba, Efunroye Tinubu remained politically active in both Lagos and Abeokuta. Subuola, Efunsetan Aniwura, Iyalode Ibadan and Feedge of Gbangan to mention a few were notable women in Yoruba society with political activism in the 1800s until the time Funmilayo Ransom Kuti who led the Egba women protest against taxation in Egba land. What were the secrets of their political activism? What lessons should contemporary women learn from their involvement in the politics of their time? These are some of the questions that this study tried to find answers to. The paper adopted historical, descriptive and empirical methods in its analysis.